Barcoding bugs: DNA-based identification of the true bugs (Insecta: Hemiptera: Heteroptera). - Doo-Sang Park (Public Library of Science (PLoS), 2011)
Background DNA barcoding, the analysis of sequence variation in the 5' region of the mitochondrial cytochrome c oxidase I (COI) gene, has been shown to provide an efficient method for the identification of species in a wide range of animal taxa. In order to assess the effectiveness of barcodes in the discrimination of Heteroptera, we examined 344 species belonging to 178 genera, drawn from specimens in the Canadian National Collection of Insects. Methodology/principal findings Analysis of the COI gene revealed less than 2% intra-specific divergence in 90% of the taxa examined, while minimum interspecific distances exceeded 3% in 77% of congeneric species pairs. Instances where barcodes fail to distinguish species represented clusters of morphologically similar species, except one case of barcode identity between species in different genera. Several instances of deep intraspecific divergence were detected suggesting possible cryptic species. Conclusions/significance Although this analysis encompasses 0.8% of the described global fauna, our results indicate that DNA barcodes will aid the identification of Heteroptera. This advance will be useful in pest management, regulatory and environmental applications and will also reveal species that require further taxonomic research.